Determination of extraframework metal content in zeolitic catalysts by means of WD XRF spectrometry - Knotek, Petr; Pouzar, Miloslav; Bulánek, Roman; Novoveská, Kateřina (Univerzita Pardubice, 2004)
XRF spectroscopy is not widely used for zeolites, but its known advantages are indispensable, i.e. small consumption of the sample (5 mg), analysis of the sample without dissolution, quickly and easy pre-treatment and low-cost analysis. Therefore, development of methodology for determination of metal (Cu, Co, Ga, V) content in zeolites using wavelength dispersive X-ray fluorescence analysis is described in this paper. XRF spectrometer was calibrated for each metal using model pellets containing oxide and boric acid. Response of detector on the amount of metal can be reliably fitted by a linear model. Copper (resp. cobalt) zeolites showed good agreement in metal content determination by XRF and standard validated analysis (AAS and ICP-OES after zeolite dissolution).